Holocene glacial evolution of Mohnbukta in eastern Spitsbergen. (24th August 2017) - Flink, Anne E.; Hill, Peter; Noormets, Riko; Kirchner, Nina
Abstract : Submarine geomorphology is one of the main tools for understanding past fluctuations of tidewater glaciers. In this study we investigate the glacial history of Mohnbukta, on the east coast of Spitsbergen, Svalbard, by combining multibeam‐bathymetric data, marine sediment cores and remote sensing data. Presently, three tidewater glaciers, Heuglinbreen, Königsbergbreen and Hayesbreen calve into Mohnbukta. Hayesbreen surged at the end of the Little Ice Age, between 1901 and 1910. The submarine landform assemblage in Mohnbukta contains two large transverse ridges, interpreted as terminal moraines, with debrisflow lobes on their distal slopes and sets of well‐preserved geometric networks of ridges, interpreted as crevasse‐squeeze ridges inshore of the moraines. The arrangement of crevasse‐squeeze ridges suggests that both landform sets were produced during surge‐type advances. The terminus position of the 1901–1910 Hayesbreen surge correlates with the inner (R.2) terminal moraine ridge suggesting that the R.1 ridge formed prior to 1901. Marine sediment cores display 14 C ages between 5700–7700 cal. a BP derived from benthic foraminifera, from a clast‐rich mud unit. This unit represents pre‐surge unconsolidated Holocene sediments pushed in front of the glacier terminus and mixed up during the 1901 surge. An absence of retreat moraines in the deeper part of the inner basin and the observation of tabular icebergs calving off the glacier front during retreat suggest that the front of Hayesbreen was close to flotation, at least in the deeper parts of the basin. As the MOH15‐01 core does not penetrate into a subglacial till and the foraminifera in the samples were well preserved, the R.1 ridge is suggested to have formed prior to the deposition of the foraminifera. Based on these data we propose that a surge‐type advance occurred in Mohnbukta in the early Holocene, prior to 7700 cal. a BP, which in turn indicates that glaciers can switch to and from surge mode.